SALA DE EXPOSIÇÕES JAVA BONAMIGO AMPLIANDO O ESPAÇO PERCEPTUAL - PINHEIRO, ALESANDRA I. D.; THALHEIMER, JANINE C.; SANTOS, MARIA S. L. D.; PROTTI, SALÉTE R.; PINHEIRO, ALESANDRA I. D.; THALHEIMER, JANINE C.; SANTOS, MARIA S. L. D.; PROTTI, SALÉTE R.; PINHEIRO, ALESANDRA I. D.; THALHEIMER, JANINE C.; SANTOS, MARIA S. L. D.; PROTTI, SALÉTE R. (Salão do Conhecimento, 2013)
Resumo